A Re‐evaluation of the Plenus Cold Event, and the Links Between CO2, Temperature, and Seawater Chemistry During OAE 2. Issue 4 (25th April 2020) - O'Connor, Lauren K.; Jenkyns, Hugh C.; Robinson, Stuart A.; Remmelzwaal, Serginio R. C.; Batenburg, Sietske J.; Parkinson, Ian J.; Gale, Andy S.
Abstract: The greenhouse world of the mid‐Cretaceous (~94 Ma) was punctuated by an episode of abrupt climatic upheaval: Oceanic Anoxic Event 2. High‐resolution climate records reveal considerable changes in temperature, carbon cycling, and ocean chemistry during this climatic perturbation. In particular, an interval of cooling has been detected in the English Chalk on the basis of an invasive boreal fauna and bulk oxygen‐isotope excursions registered during the early stages of Oceanic Anoxic Event 2—a phenomenon known as the Plenus Cold Event, which has tentatively been correlated with climatic shifts worldwide. Here we present new high‐resolution neodymium‐, carbon‐, and oxygen‐isotope data, as well as elemental chromium concentrations and cerium anomalies, from the English Chalk exposed at Dover, UK, which we evaluate in the context of >400 records from across the globe. A negative carbon‐isotope excursion that correlates with the original "Plenus Cold Event" is consistently expressed worldwide, and CO2 proxy records, where available, indicate a rise and subsequent fall in CO2 over the Plenus interval. However, variability in the timing and expression of cooling at different sites suggests that, although sea‐surface paleotemperatures may reflect a response to global CO2 change, local processes likely played a dominant role at many sites. Variability in the timing and expression of changes in water mass character, and problems in determining the driver of observed proxy changes, suggest that no single simple mechanism can link the carbon cycle to oceanography during the Plenus interval and other factors including upwelling and circulation patterns were locally important. As such, it is proposed that the Plenus carbon‐isotope event is a more reliable stratigraphic marker to identify the Plenus interval, rather than any climatic shifts that may have been overprinted by local effects. Key Points: This study is the first to review mechanistic interactions, and temporal leads and lags, between temperature, seawater chemistry, and CO2 within the Plenus interval The negative carbon‐isotope excursion during the Plenus interval was a global event driven by a CO2 increase, and appears decoupled from cooling and circulation changes Cooling was not globally synchronous; local climatic and environmental responses to the CO2 change are more complex than previously understood